2007
DOI: 10.3928/1081-597x-20070501-16
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Astigmatism of the Location of Clear Corneal Incision in Phacoemulsification of Cataract

Abstract: PURPOSE: To investigate the refractive results of clear corneal incision performed at the steepest meridian of pre-existing corneal astigmatism. METHODS: One hundred eighty-two patients with astigmatism >0.75 diopters (D) were evaluated. Superior, temporal, nasal, supe rotemporal, or superonasal clear corneal incisions were performed at the steep meridian. Refraction, visual acuity, and topography values were evaluated, and changes in surgically induced astigmatism were calculated by vector analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 9 publications
3
35
2
1
Order By: Relevance
“…An incision on the preoperative steep meridian resulted in insignificant torsion in all incision groups. Altan-Yaycioglu et al 3 evaluated the refractive results of CCIs performed at the steepest meridian in cases of astigmatism greater than 0.75 D. They conclude that the change was small with temporal incisions, whereas nasal incisions resulted in higher SIA. Kohnen et al 11 found that the induced corneal astigmatism was 0.47 D with temporal CCIs and 1.55 D with nasal CCIs.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…An incision on the preoperative steep meridian resulted in insignificant torsion in all incision groups. Altan-Yaycioglu et al 3 evaluated the refractive results of CCIs performed at the steepest meridian in cases of astigmatism greater than 0.75 D. They conclude that the change was small with temporal incisions, whereas nasal incisions resulted in higher SIA. Kohnen et al 11 found that the induced corneal astigmatism was 0.47 D with temporal CCIs and 1.55 D with nasal CCIs.…”
Section: Discussionmentioning
confidence: 96%
“…Kohnen et al 11 found that the induced corneal astigmatism was 0.47 D with temporal CCIs and 1.55 D with nasal CCIs. Altan-Yaycioglu et al 3 performed vector analysis using J0 and J45 for statistical comparison. However, this method is limited because each vector component has different implications for different steep meridians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…astigmatism (SIA) to select the correct toric IOL and calculate the optimum angle of placement Surgically induced astigmatism is a known consequence of creating the incision necessary for cataract removal and IOL implantation. 7,8 Because corneal astigmatism is a vector quantity (comprising a magnitude and a direction), simply adding and subtracting astigmatism values will not yield useful information. The amount of astigmatism to be corrected at the time of surgery must be the vector sum of the preoperative corneal astigmatism and any SIA.…”
mentioning
confidence: 99%